Potential of Microalgae as Functional Foods Applied to Mitochondria Protection and Healthy Aging Promotion - Lorenzo Zanella; Fabio Vianello (Nutraceuticals, 2023)
The rapid aging of the Western countries’ populations makes increasingly necessary the promotion of healthy lifestyles in order to prevent/delay the onset of age-related diseases. The use of functional foods can significantly help to achieve this aim, thanks to the contribution of biologically active compounds suitable to protect cellular and metabolic homeostasis from damage caused by stress factors. Indeed, the excessive production of reactive oxygen species (ROS), favored by incorrect eating and behavioral habits, are considered causal elements of oxidative stress, which in turn favors tissue and organism aging. Microalgae represent a convenient and suitable functional food because of their extraordinary ability to concentrate various active compounds, comprising omega-3 polyunsaturated fatty acids, sterols, phenolic compounds, carotenoids and others. Within cells, mitochondria are the cellular organelles most affected by the accumulation of molecular damage produced by oxidative stress. Since, in addition to producing the chemical energy for cellular metabolism, mitochondria control numerous cell cycle regulation processes, including intrinsic apoptosis, responses to inflammatory signals and other biochemical pathways, their dysfunction is considered decisive for many pathologies. Among these, some degenerative diseases of the nervous system, cardiovascular system, kidney function and even cancer are found. From this viewpoint, bioactive compounds of microalgae, in addition to possessing high antioxidant properties, can enhance mitochondrial functionality by modulating the expression of numerous protective factors and enzymes, which in turn regulate some essential biochemical pathways for the preservation of the functional integrity of the cell. Here, we summarize the current knowledge on the role played by microalgal compounds in the regulation of the mitochondrial life cycle, expression of protective and reparative enzymes, regulation of intrinsic apoptosis and modulation of some key biochemical pathways. Special attention was paid to the composition of some cultivable microalgae strains selected for their high content of active compounds suitable to protect and improve mitochondrial functions.